Factors Influencing the Success of Thai Foreign Direct Investment in ASEAN under ASEAN Comprehensive Investment Agreement - Meemak, Worapit (Rajapark Journal, 2022)
This research aimed to study investment success of Thai enterprises in ASEAN, analyze core components of the ASEAN Comprehensive Investment Agreement, and examine factors influencing investment success of Thai enterprises in ASEAN by means of samples of 246 people randomly drawn from target population, including individuals in ASEAN direct investment companies. Data collected through reliability-tested questionnaire were analyzed by one way analysis of variance, multivariate analysis of variance, and multiple regression analysis. The findings revealed that there was no difference between either individuals or types of enterprises regarding success of an investment and core components of the ASEAN Comprehensive Investment Agreement. Factors affecting the success of an investment the most were related and supporting industries, then factor conditions, business chances, ownership advantages, demand conditions, government policy, and firm strategy, structure and rivalry, respectively.